2020
DOI: 10.3389/fchem.2020.543452
|View full text |Cite
|
Sign up to set email alerts
|

Study of CO2 Adsorption on Chemically Modified Activated Carbon With Nitric Acid and Ammonium Aqueous

Abstract: The study of CO 2 adsorption on adsorbent materials is a current topic of research interest. Although in real operating circumstances, the removal conditions of this gas is carried out at temperatures between 290 and 303 K and 1 Bar of pressure or high pressures, it is useful, as a preliminary approach, to determine CO 2 adsorption capacity at 273K and 1 Bar and perform a thermodynamic study of the CO 2 adsorption heats on carbonaceous materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Among the three samples C-0 showed that maximum adsorption capacity with adsorption values of 97.98, 97.55, 96.34, 97.45, 95.34 mg/g respectively. It was expected an increase in the CO 2 adsorption for N-doped activated carbons as reported in previous studies [44,45]. The basic nitrogen functionalities react with the Lewis acidic CO 2 to increase the chemisorption to a greater extent.…”
Section: N 2 Adsorption Desorption Isothermsupporting
confidence: 64%
“…Among the three samples C-0 showed that maximum adsorption capacity with adsorption values of 97.98, 97.55, 96.34, 97.45, 95.34 mg/g respectively. It was expected an increase in the CO 2 adsorption for N-doped activated carbons as reported in previous studies [44,45]. The basic nitrogen functionalities react with the Lewis acidic CO 2 to increase the chemisorption to a greater extent.…”
Section: N 2 Adsorption Desorption Isothermsupporting
confidence: 64%
“…Concerning to the modification of AC with APTMS, a decrease in BET area and pore volume of mAC up to 188 m 2 /g and 0.490570 cm 3 /g respectively, in relation to non- chemically modified AC. The formation of new surface functional groups attributed as the major obstruction for the drastic decrease in surface area [ 60 ]. Similar results have shown that formation of surface functional groups like nitriles, amides, amines, among others block the existing pores and reduce the surface are upon chemical modification of carbonaceous material [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…20-21 µmol•m −2 as defined by the CRC/Surface area ratio [17]. Compared to various highly porous materials [9][10][11][12][13][14][15][16]41] this value is lower than that of activated carbons (ca.…”
Section: Affinity Improvement Towards Comentioning
confidence: 99%
“…Other CO 2 capture attempts were performed with materials such metal-inorganic-organic core-shell material [9], chemically modified activated carbon with nitric acid and ammonium aqueous solutions [10], cupric nitrate [11] or polyacrylonitrile [12], functionalized carbonaceous and silica-based materials [13], zeolites and layered double hydroxides [14][15][16], metal-organic frameworks (MOFs), mesoporous silica, clay, porous carbons, porous organic polymers (POP), and metal oxides (MO) [16]. Most of these materials involve costly/sophisticated synthesis procedures but low surface affinity as reported to their specific surface area as defined earlier [17].…”
Section: Introductionmentioning
confidence: 99%